Integration of digital tools in teaching math at academic lyceums (Eurasian Scientific Herald, 2024)
This scientific article explores the integration of digital tools in teaching mathematics at academic lyceums, aiming to enhance students' learning experiences and develop their mathematical competencies. The study investigates the benefits, challenges, and effective strategies for incorporating digital tools into math instruction. It also examines the impact of digital tools on student engagement, problem-solving skills, and conceptual understanding. Findings indicate that the integration of digital tools in math education at academic lyceums positively influences student learning outcomes and prepares them for the demands of the digital era. Recommendations for educators and policymakers are provided to support the effective implementation of digital tools in mathematics classrooms